In vitro regeneration of semecarpus anacardium L. from axenic seedling-derived nodal explants - Panda, Bhuban Mohan; Hazra, Sulekha (Trees-Structure and Function, 2010)
Semecarpus anacardium (Anacardiaceae), a deciduous forest tree, is a potent source of medicinal compounds. Poor seed viability of this species limits the conventional propagation practice. Proliferation of shoots from axillary meristem was achieved in semisolid WPM medium supplemented with BAP 4.44 mu M and KN 4.64 mu M. Factors including culture vessels, gelling agents and antioxidants were identified and optimized for proliferation and growth of shoots in vitro. Cotton-plugged culture vessels were more favorable. Phytagel 0.2% as gelling agent and activated charcoal 0.2% as antioxidant were superior to other agents and antioxidants tested. All the shoots rooted in half-strength WPM liquid medium with IBA 2.46 mu M. Rooted shoots survived (91%) in the soil-sand 1:1 mixture. Ex vitro rooting of shoots and hardening of plants were achieved in 80% of the explants in the soil-sand mixture. Hardened plants were maintained in a greenhouse. This is the first report on in vitro regeneration of Semecarpus anacardium.
Keywords: Antioxidants; Culture vessels; Ex vitro rooting; Gelling agents; Medicinal tree; micropropagation

In vitro morphogenic response in cotyledon explants of semecarpus anacardium L. - Panda, Bhuban Mohan; Hazra, Sulekha (Plant Biotechnology Reports, 2012)
Three different morphogenic responses-caulogenesis, direct somatic embryogenesis, and callusing-were noted in cotyledon explants of Semecarpus anacardium L. cultured in woody plant medium (WPM) containing thidiazuron (TDZ). Thidiazuron, at all concentrations tested, induced organogenic as well as embryogenic responses. The organogenic buds differentiated to shoots and the embryogenic mass (EM) gave rise to globular embryos which differentiated up to cotyledon-stage embryos on repeated culture in growth regulator (GR)-free WPM medium containing 0.2% activated charcoal after the removal of TDZ. The organogenic and embryogenic responses were optimal in 9.08 mu M TDZ after the removal of TDZ. Elongated shoots rooted in half-strength liquid WPM medium with 2.46 mu M indole butyric acid. Plants were successfully acclimatized and transferred to soil. Histological studies confirmed the direct origin of the organogenic buds from the cotyledon explants. The EMs produced somatic embryos on repeated culture in charcoal incorporated GR-free medium. Morphogenic callus formation from the cotyledon explants was also noted. This callus on repeated culture in WPM medium with charcoal differentiated into somatic embryos. Repetitive somatic embryogenesis was evident from direct and indirectly formed primary embryos. The somatic embryos did not convert into plantlets, though sporadic germination of embryos was observed through the emergence of roots.
Keywords: callus; Caulogenesis; Globular embryos; Growth regulator; Histology; somatic embryogenesis